Comparison of the psychoactive activity of four primary Areca nut alkaloids in zebrafish by behavioral approach and molecular docking - Siregar, Petrus; Audira, Gilbert; Castillo, Agnes L.; Roldan, Marri Jmelou M.; Suryanto, Michael Edbert; Liu, Rong-Xuan; Lin, Ying-Ting; Lai, Yu-Heng; Hsiao, Chung-Der (Biomedicine & pharmacotherapy, 2022)
Areca palm nut (Areca catechu) has been listed as one of the most addictive substances, along with tobacco, alcohol, and caffeine. It belongs to the family Arecaceae and is widely used in Asia. Areca nut contains seven psychoactive alkaloids; however, the effects of these alkaloids on behaviors are rarely to be addressed in zebrafish. Therefore, this study aims to compare the psychoactive and potential adverse effects of four primary alkaloids (arecoline, arecaidine, guvacine, and guvacoline) isolated from areca nut on zebrafish. We found that four alkaloids induced hyperactivity-like behaviors in zebrafish larvae. Cooperating the results with the previous study, molecular docking scores suggested these alkaloids might bind to multiple muscarinic acetylcholine receptors (mAChRs), and various best binding modes were shown. According to the adult zebrafish behavioral test, arecoline was found to slightly increase the locomotor activity and caused tightening shoaling formations of adult zebrafish. Meanwhile, zebrafish exposed to arecaidine have reduced aggressiveness and conspecific social interaction. Similar to arecaidine, guvacoline treatment also caused abnormalities in zebrafish social behaviors. Furthermore, the fish displayed abnormal exploratory behaviors after being exposed to guvacoline. Interestingly, altered fear response behaviors were only displayed by guvacine-treated fish besides their lower locomotor activity. Based on the results of molecular docking, we hypothesize that the behavior alterations might be a consequence of the interaction between alkaloids and multiple mAChRs in the nervous system. In summary, our study found that each alkaloid specifically affects adult zebrafish behaviors. [Display omitted]